Material Flow Cost Accounting in Czech Environment - Dana Kovanicová (European Financial and Accounting Journal, 2011)
The theme of article is the draft of ISO 14051-Environmental Management – Material flow cost accounting – General framework, whose final form should be finished at the end of 2011 or later. This standard does not take in consideration the national particularity. Therefore, the main aim of this paper is to review how the concept of MFCA meets the Czech conditions. The MFCA (as one of cost accounting methods) is in Czech Republic a part of management accounting (MA), which coincides with the Anglo- Saxon concept. MA is a skeleton for other components of information system, closely connected with the physical process. The environmental management accounting (EMA) is based on the same concept: it could be defined as a “green MA”. When defining EMA, we encounter many misleading inaccuracies and misunderstandings. Firstly, some believe that traditional management accounts generally detect only actual costs. From this, MFCA is defined as a (solely) accounting method. Secondly, EMA is segmented to physical part (PEMA) and monetary part (MEMA). This leads to obscure the substance of EMA. Implementation of costing methods has a long tradition in Czech Republic. Basic types of traditional costing methods (unlike MFCA) have been derived from the conditions, under which specific production process continues. MFCA adoption in our conditions should be comprehended as an upgrading and enhancement of the traditional methods, not as their suppression.
Keywords: M41; Q56; 650; Material Flow Cost Accounting; Costing; Management Accounting; Environmental Management Accounting